2020
DOI: 10.1111/php.13293
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Inactivation of Coronaviruses by Solar Radiation With Special Reference to COVID‐19

Abstract: Using a model developed for estimating solar inactivation of viruses of biodefense concerns, we calculated the expected inactivation of SARS-CoV-2 virus, cause of COVID-19 pandemic, by artificial UVC and by solar ultraviolet radiation in several cities of the world during different times of the year. The UV sensitivity estimated here for SARS-CoV-2 is compared with those reported for other ssRNA viruses, including influenza A virus. The results indicate that SARS-CoV-2 aerosolized from infected patients and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
148
5
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(185 citation statements)
references
References 45 publications
15
148
5
5
Order By: Relevance
“…The effect of natural and arti cial UV on virus inactivation has been extensively studied. For example, the in uenza virus is inactivated by up to 99% if exposed to full sunlight during a single day in Mexico City, but this value lowers to 66% in the winter (Sagripanti and Lyte 2007;Sagripanti and Lytle 2020). Another study demonstrated that aerosolized MHV Coronavirus could be highly sensitive to 254 nm UV-C, but it is dependent on the culture medium (Walker and Ko 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of natural and arti cial UV on virus inactivation has been extensively studied. For example, the in uenza virus is inactivated by up to 99% if exposed to full sunlight during a single day in Mexico City, but this value lowers to 66% in the winter (Sagripanti and Lyte 2007;Sagripanti and Lytle 2020). Another study demonstrated that aerosolized MHV Coronavirus could be highly sensitive to 254 nm UV-C, but it is dependent on the culture medium (Walker and Ko 2007).…”
Section: Discussionmentioning
confidence: 99%
“…to 37% of the initial value), and is written as D 37,UVC [6]. Based on genome size, for Coronaviridae , they estimated D 37,UVC between 2.5-3.9 J/m 2 , and D = 3.0 J/m 2 for SARS-CoV-2 [7]; this value is used in the calculations presented here. Although no UVC reaches the Earth’s surface, longer wavelengths can still affect viral RNA, albeit with decreased sensitivity.…”
Section: Methodsmentioning
confidence: 99%
“…Sagripanti & Lytle [7] later calculated inactivation rates for SARS-CoV-2, for several worldwide locations at different times of the year. As will be shown later in Figure 1, the experimentally observed inactivation rates in [2,3] are significantly faster than predicted by the model in [6,7]. In addition, the observed dependence on the medium composition is not consistent with this medium-independent model.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations